AXIOLOGICAL ASPECTS OF THE FINANCIAL LAW SYSTEM - Imeda A. Tsindeliani (RUDN Journal of Law, 2020)
Legal axiology, as a scientific discipline, allows us to consider both the legal system of the State as a whole, and its individual elements from the point of view of the value foundations that exist in society and in each individual. The consideration of the elements of the State's legal system through value categories allows us to determine the relationship and interdependence of all elements of the legal system. It is especially necessary to note the influence of value categories on the formation of a system of the separate branches of the law, including the financial law of Russia. Value categories have an influence not only on the formation of the elements of the financial law system, but also predetermine their interaction as legal means of regulation of the public finances. The elements of the financial law system, as a branch of law, are the principles of the financial law, the rules of the financial law, and their separate forms of grouping - institutions and sub-sectors of the financial law. The principles of the financial law are the direct legal regulators of public relations in the field of public finance by their nature. Possessing regulatory properties, the principles of the financial law shouldn’t be identified with the rules of the financial law, since they are independent legal means of the regulation. The principles of the financial law, on the basis of their regulatory properties, should be considered as elements of a system of the financial law.